Determinan sosial dan cakupan pemberian vaksin inactivated polio vaccine (IPV) di kota Cimahi - Ahmad, Nasir; Syuhada, Ambar Dani (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: In West Java the coverage of the IPV vaccine in 2018 was quite low, namely 51.16%. In the City of Cimahi in 2017 there was a target of 10,974 babies with a coverage of 3,063 (27.91%), in 2018 the target was 10,848 coverage 5,707 (52.6%) and in 2019 the target to be achieved was 10,777 babies. In the City of Cimahi until 2019, data, both research results and published survey results, have not been found that can be used as a reference to provide an overview of the results of the implementation of the IPV vaccine. Objective: To find out the coverage of IPV vaccine and the most dominant determinant of the completeness of IPV administration. Method: The study design used was cross-sectional. The sample size in the study was 193 children aged 12-24 months who were selected using cluster random sampling technique. The data were collected by means of interview techniques using structured questionnaires and observations. Data analysis used univariate, bivariate and multivariate analysis.The number of samples studied was 35 respondents, the sample was selected using total sampling technique. Data collection was carried out by interview techniques using structured questionnaires and observations. Data analysis uses the kai-square test. Results: The coverage of IPV provision in the city of Cimahi in 2019 was 73.6%. The significant variables were mothers who worked (PR = 2,140 and ρ = 0.026) and mothers who had low knowledge (PR = 2.881 and ρ = 0.004). The multivariate result of the most dominant variable was maternal knowledge Exp (B) = 2,917. Conclusion: Several reasons for not providing IPV were because they did not know the information, did not have time, IPV was not available, was not allowed by husbands and reasons of trust. Suggestions for the Health Office to prioritize the provision of information related to IPV and optimizing the role of kader in providing education or understanding of IPV